UTAUT-Based Analysis of Customer Loyalty in Tokopedia Using SOR Framework - Cindy Berliana; Eristya Maya Safitri; Tri Puspa Rinjeni (Komunitas Dosen Indonesia, 2025)
This study investigates customer loyalty in the context of e-commerce by applying an integrated Unified Theory of Acceptance and Use of Technology (UTAUT) model combined with the Stimulus–Organism–Response (SOR) framework. Tokopedia, one of Indonesia’s leading e-commerce platforms, faces increasing difficulty in sustaining customer loyalty due to common service-related issues such as delayed deliveries, system errors during voucher usage, and slow customer service. These challenges negatively impact user experience and trust key elements in fostering long-term loyalty. To address these issues, this research explores the need for an integrated approach by employing the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Stimulus–Organism–Response (SOR) framework. The UTAUT model provides insights into the factors driving user adoption, while the SOR framework helps in understanding the psychological responses that lead to sustained loyalty. This research explores how five UTAUT constructs Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, and Price Value serve as external stimuli (Stimulus) that influence users’ trust in the Tokopedia application (Organism), which then drives customer loyalty (Response). A quantitative survey of 384 Tokopedia users was analyzed using PLS-SEM. The findings reveal that all UTAUT variables significantly affect trust, and trust serves as a strong predictor of customer loyalty. This study contributes theoretically by bridging UTAUT and SOR models to explain loyalty behavior in e-commerce settings, and offers practical insights for Tokopedia to improve user retention. Notably, future studies may consider longitudinal approaches and explore additional psychological factors beyond trust to deepen understanding of loyalty formation.